Platelet Rich Plasma Injection for Treatment of Neuropathy After Hernia Repair - Tantri, Aida Rosita; Asmara, Yoseph Rohedi; Kwan, Lawrence (Writing Center IMERI FMUI, 2023)
A young male patient developed persistent severe right-sided groin and scrotal pain following hernia repair. After two months of failed conservative therapy, he was referred to the pain clinic. Genitofemoral Neuralgia was suspected because the area of pain corresponds to the innervation area of the Genitofemoral nerve. For diagnostic and therapeutic purposes, it was injected with local anesthetic and steroid using ultrasound guidance. The initial injection led to pain relief for one month. There are some choices for treating neuralgia after a confirmatory diagnostic block, such as neurolysis, pulsed radiofrequency, or surgical neurectomy. We chose Platelet Rich Plasma (PRP) injection because it has the potential for nerve regeneration and is less invasive. Ultrasound allows for controlled administration and greatly enhances the technical ability to perform precise localization and injection. The patient, in this case, has more than 50% pain reduction after PRP therapy. He no longer needs medication and can return to normal daily activities. This case report illustrates the first presentation of managing post-herniorrhaphy neuropathy using Platelet Rich Plasma.